Formaciones salinas de las cuencas triásicas en la Península Ibérica: caracterización petrológica y geoquímica. - Rosell, L.; Utrilla, R.; García- Veigas, J.; Jurado, M.J.; Orti Cabo, F. (Cuadernos de Geología Ibérica, 1996)
Triassic salt and anhydrite samples coming from boreholes and in mínor degree from mine galleries and outcrops are studied. Lithofacies and textural characteristics of halite suggest the existence of recrystallization processes leading to the loss of primary features such as hopper and chevrons, which are in part synsedimentary (early diagenetic) and in part of deep burial origin. Moreover, in the diapiric zones recrystallization becomes severe and brecciation appears very frequently. Both bromine content of balite and isotopic composition of anhydrite are relatively homogeneous in the various basins studied, thus proving the marine origin of mother brines and a stable inflow from the ocean, despite the fact that sedimentation took place in generallized transitional environments. According to these textures and geochemical contents, and in comparison with those exhibited in other Triassic basins of Europe and North África, it can be stated that conditions governing salt precipitation in the Iberian Peninsula during Triassic times were rather uniform and corresponded to shallow basins in wich the possible influence of continental water can not be proved from the geochemical point of view. Important chloride and sulphate accumulations recorded in these basins may be held as the best indicator of continuous subsidence controlled by the Triassic rifting.